Embryonic stem cells: An alternative approach to developmental toxicity testing - S Tandon; S Jyoti (Wolters Kluwer Medknow Publications, 2012)
Stem cells in the body have a unique ability to renew themselves and give rise to more specialized cell types having functional commitments. Under specified growth conditions, these cell types remain unspecialized but can be triggered to become specific cell type of the body such as heart, nerve, or skin cells. This ability of embryonic stem cells for directed differentiation makes it a prominent candidate as a screening tool in revealing safer and better drugs. In addition, genetic variations and birth defects caused by mutations and teratogens affecting early human development could also be studied on this basis. Moreover, replacement of animal testing is needed because it involves ethical, legal, and cost issues. Thus, there is a strong requirement for validated and reliable, if achievable, human stem cell-based developmental assays for pharmacological and toxicological screening.